Industrialiser la méthanisation agricole. Les reconfigurations d’une filière soumise aux exigences de production et de rentabilité - Antoine Bouzin (Développement Durable et Territoires)
The 2010s saw a transformation in the framing of public policies relating to methanization. In 2013, the Énergie Méthanisation Autonomie Azote plan, led by the Ministries of Agriculture and Ecology, presented anaerobic digestion as a solution to a range of public problems – energy, climate, waste treatment, economic, agri-environmental – and appointed farmers to lead the industry. However, by the end of the 2010s, the government’s expectations had become more focused on energy and climate issues. The priority given to energy production is coupled with other budgetary expectations involving requirements in terms of industrialization and profitability – in short, a frame of reference that is congruent with the principles of ecological modernization. In addition, the spread of injection methanization models and the reduction in feed-in tariffs scheduled for 2020 are tending to impose a new economic model on the sector. While the increase in investment costs is complicating access to the sector for farmers, the energy industry is demonstrating its willingness to enter the sector, and is setting substantial production targets. It is both the definition of legitimate methanization models and the image of the sector itself, and its role in society, that are the subject of a struggle crystallized by the twofold competition between cogeneration and injection units, on the one hand, and between agricultural units and centralized units, on the other.